วิ่งเพื่อรับผิดชอบต่อสังคม - โฆษิตวรวุฒิ, พรเทพ (วารสารศรีล้านช้างปริทรรศน์; Vol 5 No 1 (2019): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 5 ฉบับที่ 1 (มกราคม - มิถุนายน 2562), 2019)
บทความวิชาการฉบับนี้มีวัตถุประสงค์เพื่อศึกษาการวิ่งเพื่อรับผิดชอบต่อสังคม จากการศึกษาพบว่า เกิดจาก 3 สาเหตุ ได้แก่ สุขภาพ การช่วยเหลือสังคม และเครือข่ายความร่วมมือ ด้วยเหตุนี้รัฐบาลควรกำหนดนโยบายเรื่องของการบูรณาการเรื่องของการออกกำลังกายในรูปแบบต่าง ๆ บรรจุไว้ในแผนงานสู่การปฏิบัติโดยผู้บริหารขององค์กร และควรเปิด โอกาสให้บุคลากรในองค์กรและผู้มีส่วนได้เสียมีส่วนร่วมในการจัดทำโครงการต่าง ๆ เป็นประจำ This research objective is to study the run for corporate social responsibilities. It is found that caused by 3 reasons, namely healthy, social service activities and collaboration network. Therefore, the government should establish a policy on the integration of various forms of exercise. Strategy Implementation by the director of the organization and Should provide opportunities for personnel in the organization and stakeholder participated in various of project, regularly.